Insight into the Interaction of Cationic Porphyrin-Anthraquinone Hybrids with Hsp90: In Silico Analysis - Muhammad Arba; Ruslin Ruslin; Rahmana Emran Kartasasmita; Slamet Ibrahiim; Daryono Hadi Tjahjono (Journal of Mathematical and Fundamental Sciences, 2018)
Heat shock protein 90 (Hsp90) is responsible for the correct folding of many cellular proteins. Several Hsp90 inhibitors have been developed for cancer treatment. The present in silico study aimed to evaluate the potential of several porphyrin derivatives conjugated with anthraquinone groups as Hsp90 inhibitors by using simulation of molecular docking and molecular dynamics. The binding mode of porphyrin hybrids to Hsp90, which was examined by using AutoDock 4.2, showed that all six porphyrin compounds fit well in the binding pocket of Hsp90. The pi-cationic interactions with Lys58 were exclusively observed in the interaction of each porphyrin hybrid. Stabilities of porphyrin-Hsp90 complexes were confirmed by 40-ns MD simulation, which was carried out with the help of AMBER16. Prediction of ligand affinity by using the MM-PBSA method showed that all complexes were energetically favorable as indicated by a negative binding free energy. The predicted affinities of tris−H2PyP−AQ, tris−H2PzP−AQ, bis−H2PzP−AQ, and mono−H2PzP−AQ are better than those of geldanamycin, a known inhibitor of Hsp90, which shows the importance of the electrostatic and van der Waals energies for ligand binding.